(untitled) (Journal of the College of Languages (JCL), 2019)
This paper tackles in detail the functional shift of parts of speech, such as the shift of a verbal clause to an adjectival clause, along with the types of such a shift. The researcher identified the important features of participles, as well as the concept of participles, adjectives, and their types. Also, the most important changes that affect the participles during such shifts. Further, an exposition is made of the different producers through which a verbal clause is changed into an adjectival one in Russian. This type of functional shift in parts of speech is seen as a process of deriving most of the new words in contemporary Russian. Russian is very rich in new words, whether by way of processes of derivation or by borrowing and acclimatization of foreign words, or by making a functional shift of a certain part of speech into another; or, by other ways which would contribute to add to the stockpile of Russian words. Аннотация Данная статья под названием" Функциональная транспозиция причастий в прилагательное " посвящена объяснению проблемы функциональная транспозиция частей речи – причастие и типы транспозиции, а так же основные характиристики и типы и причастие и прилагательное. В нашей работе рассматриваютсясемантические и синтаксические изменения причастия при переносе в разряд прилагательных и при помощи их объяснили динамичные способы измения при транспозиции. Переход одну часть речи в другую, является одним из важных методов образования болшинство новых слов в русском языке. Русский язык богата новыми словами помощью способов словообразования , заимствования иностранных слов через другого языка и адаптация их функциональная транспозиция одну части речи в другой и др., которые активно так или иначе обогащают словарного состава современного русского языка.